Heating rate and spin flip lifetime due to near-field noise in layered superconducting atom chips - Fermani, R. (2014)
We investigate theoretically the heating rate and spin flip lifetimes due to near-field noise for atoms trapped close to layered superconducting structures with the superconductor in the Meissner state. In particular, we compare the case of a gold layer deposited above a superconductor with the case of a bare superconductor. We study a niobium-based and a YBa2Cu3O7 − x (YBCO)-based chip. For both niobium and YBCO chips at a temperature of 4.2 K, we find that the deposition of the gold layer can have a significant impact on the heating rate and spin flip lifetime, as a result of the increase of the near-field noise. At a chip temperature of 77 K, this effect is less pronounced for the YBCO chip.